The rice crisis : markets, policies and food security - Dawe, David (Earthscan, 2010)
Examines how government policies caused and responded to soaring world prices in the particular case of rice. This book includes comparable case studies of policy reactions in different countries that provide the understanding necessary to evaluate the impact of trade policy on the food security of poor farmers and consumers